Advocating people on food wastage through public service announcement: case study in Bukit Antarabangsa / Najihah Razman - Razman, Najihah (2018)
Food wastage is an issue that people take it lightly, somehow this issue can lead to bad behavior and unfriendly environment. In Malaysia, people go on a food wasting spree without remorse. It influences the greater part of our lives and will influence us for quite a long time to come. People need to understand what happens if they keep on being irresponsible and ignorance towards food that they wasted, and only then will they get a better understanding of what is at stake and start to manage their waste better. This research is to analyze the issues that the government has been faced with food wastage effects the authority that must be solved. Other than that, from this research is to observe the behavior of people in a certain area which Bukit Antarabangsa has been chosen as the place for me to do my case study on food wastage issue. This behavior might be influenced by some social factors as social proof and diffusion of responsibility. From the questionnaire that has been distributed, it can analyze what is the factors that lead people to wasting food. And from the result from observation and questionnaire that has been taken and what food do people usually people throw away, the researcher will create awareness by using advertising as a platform. In another way, is to educate Malaysian people to be more responsible in preventing on food wastage practice.